Classifying Ischemic Stroke, from TOAST to CISS - Chen, Pei‐Hao (CNS Neurosci Ther, 2012)
SUMMARY  Ischemic stroke classification is critical in conducting basic research and clinical practice. A precise analysis of stroke subtypes requires the integration of clinical features, findings from diagnostic tests, and knowledge about potential etiologic factors by competent diagnostic investigators. We performed a literature review of the published stroke classification systems and examined each for its benefits and limitations in the evaluation of the stroke etiology. Two major approaches to etiologic classifications of ischemic stroke are currently being used: the causative and phenotypic subtyping. The most widely used causative system is the Trial of Org 10172 in acute stroke treatment (TOAST) classification. With the advances in modern diagnostic technology, new stroke subclassification systems, such as the causative classification system (CCS) and Chinese ischemic stroke subclassification (CISS) system, have been developed to enhance the accuracy of TOAST. The A‐S‐C‐O (Atherosclerosis, Small‐vessel disease, Cardiac source, Other cause) phenotypic classification system makes efforts to identify the most likely etiology but not neglecting the possibility of other potential multiple causes. We conclude that the ideal stroke classification system needs to be valid, easy to use, evidence‐based, and incorporate new information as it emerges.